Honey bees - Sexton, Colleen A., 1967- (Minneapolis, MN : Bellwether Media, 2007)
"Simple text accompanied by full-color photographs give an upclose look at honey bees. Intended for kindergarten through third grade students"--Provided by publisher.
What is a honey bee -- Parts of a honey bee -- Honey bees and flowers -- In the hive.
Includes bibliographical references and index.
Keywords: Honeybee -- Juvenile literature